The plastid genome of an oil plants Cinnamomum chago (Lauraceae). Issue 1 (2nd January 2019) - Chen, Huanhuan; Liu, Chao; Han, Lihong; Song, Yu; Tang, Lizhou
Abstract: Cinnamomum chago B.S. Sun & H.L. Zhao is an economically important wild woody oil plant of the genus Cinnamomum Trew belonging the family Lauraceae. To better determine its phylogenetic location with respect to the other Cinnamomum species, the complete plastid genome of C. chago was sequenced. The whole plastome is 152, 753 bp in length, consisting of a pair of inverted repeat (IR) regions of 20, 074 bp, one large single-copy (LSC) region of 93, 722 bp, and one small single-copy (SSC) region of 18, 883 bp. The overall GC content of the whole plastome is 39.2%. Further, maximum likelihood phylogenetic analyse was conducted using 12 complete plastomes of the Lauraceae, which support the close relationship between C. chago and C. verum .